Challenges and innovations in 3D printed bio-organs and their materials - M., Adam Khan (Springer Nature, 2025)
This book provides an in-depth analysis of current advancements in bio-additive manufacturing. This edited volume consolidates contributions from international experts, addressing both fundamental principles and contemporary challenges in the field. The book covers a wide range of topics, including biomaterials, smart manufacturing of implants, medical interventions, post-processing techniques, and bio-printing of tissues and organs. Specific chapters focus on the characterization and design of biomaterials, advancements in ceramics, and the integration of robotics and sensors in bio-manufacturing.